MEWUJUDKAN DEMOKRASI EKONOMI DENGAN USAHA KECIL MENENGAH KOPERASI - L. SALUSINUS L. SALUSINUS (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
Cooperative Small Medium Business have two especial mission that is service to its member and improve company growth itself. To increase service its member, company earns to make member as potential market segment for the service improvement. But if we like to improve company growth, management have to orient to its member. Of course, the transaction proportion with member have to be more a lot of compared to a transaction proportion with non member, cause of however service mission to member have to be more be majored from at mission of company growth of cooperative small medium business. Result of effort obtained by transacting in external market will be more precisely be used for development of company, cause progressively expand the company indirectly also will improve its member prosperity. Growing prosperity this enabled since company earn to provide its member requirement maximally.